PENATAAN KAWASAN PENGOLAHAN IKAN BERBASIS KOMUNITAS DI KAMPUNG PESISIR MUARA ANGKE - Amnah Amnah; Tony Winata (Jurusan Arsitektur dan Perencanaan, 2026)
Muara Angke, particularly the Tembok Bolong settlement, is known as a traditional open-air fish-drying area that forms an integral part of residents’ daily activities. However, this practice generates several issues, including strong odors, accumulated fish waste, and limited access to proper communal spaces. In response to these challenges, this study aims to formulate a spatial design concept that improves environmental quality while supporting home-based fish-processing activities in a more organized manner. The research employs direct observation of residents’ daily routines, mapping of kampung activities, and an understanding of local practices as the foundation for spatial planning. Field findings are then combined with literature on participatory architecture and coastal environmental management to construct a relevant design framework. The results present a design concept that integrates fish-production areas, drying spaces, waste-processing facilities, cooperatives, and community spaces into a cohesive system aligned with kampung life. This approach creates a cleaner, more productive, and socially engaging environment. The main finding highlights that integrating fish-waste processing into spatial design can support the sustainable development of fishing communities without diminishing their local identity. Keywords: Coastal Settlement Regeneration; Coastal Village; Muara Angke; Participatory Architecture; Tembok Bolong Village Abstrak Kawasan Muara Angke, khususnya Kampung Tembok Bolong, merupakan pusat aktivitas penjemuran ikan asin secara tradisional di ruang terbuka. Kegiatan ini menjadi bagian dari rutinitas warga, namun menimbulkan persoalan seperti bau menyengat, penumpukan limbah ikan, serta keterbatasan ruang komunal yang layak. Berdasarkan isu tersebut, penelitian ini bertujuan merumuskan konsep penataan kawasan yang mampu meningkatkan kualitas lingkungan sekaligus mendukung aktivitas pengolahan ikan sebagai usaha rumahan yang lebih tertata. Pendekatan penelitian dilakukan melalui observasi langsung kehidupan sehari-hari warga, pemetaan aktivitas kampung, dan identifikasi kebiasaan lokal sebagai dasar perancangan. Temuan lapangan kemudian dianalisis bersama literatur terkait arsitektur partisipatif dan pengelolaan lingkungan pesisir untuk membangun kerangka desain yang relevan. Hasil penelitian menghasilkan konsep rancangan yang mengintegrasikan ruang produksi ikan, area pengeringan, sistem pengolahan limbah, koperasi, dan ruang komunal dalam satu kesatuan yang selaras dengan pola hidup kampung. Konsep ini menciptakan lingkungan yang lebih bersih, produktif, dan ramah bagi interaksi sosial. Temuan utama menunjukkan bahwa integrasi pengolahan limbah ke dalam desain ruang dapat mendorong kampung nelayan berkembang secara berkelanjutan tanpa menghilangkan identitas lokalnya.